IMPORTANCE OF PSYCHOLINGUISTICS IN LANGUAGE LEARNING AND TEACHING - Ergasheva Ra’no Rustam qizi; Haydarova Kamola Davranovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This thesis explores the description of many hypotheses that describe how a person learns, creates, and interprets spoken and written language have been offered by psycholinguistics. Language teachers have applied the theory in their work. They serve as the foundational beliefs for language instruction approaches developed by certain professionals. The approach is referred to as psycholinguistics. The psycholinguistic approach sees learning as an internal, cognitive process that occurs in the person before moving on to the social realm. Some approaches, such the natural method, the entire physical response technique, and the suggestopedia method, were created based on theories related to psycholinguistics. This thesis aims to open main psycholinguistic features that help teachers to consider the use of appropriate method to teach that four language skill.